Untersuchung der Faktoren, die hinsichtlich des Burn-outs von westungarischen Pädagogen von Bedeutung sind - Kissné Geosits, Beatrix (European Journal of Mental Health, 2010)
A Study of Factors Influencing Burnout in Teachers in Western Hungary: It is obvious to professionals employed in teaching and education that over the course of their work they continuously need to face a multitude of emotional reactions from children and adults, and need to address the reasons and effects of such. Thus, it is important for them to be knowledgeable of the factors that render easier or more difficult the education process itself, their work, and the conscious ways of combating these difficulties; this, while staying psychologically and emotionally functional both in their work and in their private life. In their helping profession, their most important tool is obviously their own personality. It is important for them to be able to help others, but it is equally important to be able to take care of themselves, these being the two sides of the same process. A person’s emotional life affects others – therefore it is not simply a private issue – whereas others, their circumstances, and their way of life affect the state of their inner self. This study set the goal of examining the factors influencing burnout in teachers. It therefore focuses on certain elements of choosing a profession, interests, needs, the relationship between the individual and the environment, parental upbringing attitudes, career patterns in the family, and satisfaction about career choice. Through the question of work and mental health, the author examines the degree to which professional, financial, and moral recognition influence burnout, the impact of the relationship with colleagues and the manager on the risk of burnout, and the connection between symptoms of physical health (days off work / sick leave) and mental health. The author further refines the issue studied along factors of sex, years spent in the profession, and manager / employee status.